2019
DOI: 10.1126/science.aaw4144
|View full text |Cite
|
Sign up to set email alerts
|

The heme-regulated inhibitor is a cytosolic sensor of protein misfolding that controls innate immune signaling

Abstract: Multiple cytosolic innate sensors form large signalosomes after activation, but this assembly needs to be tightly regulated to avoid accumulation of misfolded aggregates. We found that the eIF2α kinase heme-regulated inhibitor (HRI) controls NOD1 signalosome folding and activation through a process requiring eukaryotic initiation factor 2α (eIF2α), the transcription factor ATF4, and the heat shock protein HSPB8. The HRI/eIF2α signaling axis was also essential for signaling downstream of the innate immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
116
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 40 publications
7
116
1
Order By: Relevance
“…We found that mRNA translation in DCs, differently to what has been shown during chronic ISR , is mediated despite high p-eIF2α levels by an eIF4F-dependent mechanism. We also found that primary DCs, conversely to macrophages, do not rely on eIF2α phosphorylation to activate cytokines transcription nor IL-1β secretion in response to MAMPs (Abdel-Nour et al, 2019), (Chiritoiu et al, 2019). Importantly, GADD34 antagonizes PERK activity to maintain functional protein synthesis levels in non-activated DCs.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…We found that mRNA translation in DCs, differently to what has been shown during chronic ISR , is mediated despite high p-eIF2α levels by an eIF4F-dependent mechanism. We also found that primary DCs, conversely to macrophages, do not rely on eIF2α phosphorylation to activate cytokines transcription nor IL-1β secretion in response to MAMPs (Abdel-Nour et al, 2019), (Chiritoiu et al, 2019). Importantly, GADD34 antagonizes PERK activity to maintain functional protein synthesis levels in non-activated DCs.…”
Section: Introductionmentioning
confidence: 70%
“…In macrophages, p-eIF2a-and ATF4-dependent expression of HSPB8 is required for the assembly of signaling adaptors such as mitochondrial antiviral-signaling protein (MAVS), or TIR domain-containing adapter protein inducing interferon-a (TRIF), but not of Myeloid Differentiation Primary Response Gene 88 (MyD88). HSPB8 seems necessary for TRIF and MAVS to be incorporated into protein aggregates that constitute signalosomes for different innate immunity signaling pathways triggered by MAMPs (Abdel-Nour et al, 2019). Given the lack of ATF4 synthesis and the resistance of active DCs to mount an acute ISR, we investigated their capacity to produce pro-inflammatory cytokines and type-I IFN in a perturbed eIF2a-phosphorylation context.…”
Section: Importance Of the Isr For Innate Receptors Signaling In Dcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex formation, stability and signal transduction are tightly controlled through numerous other proteins reviewed elsewhere . These regulatory mechanisms include the newly discovered role of heat‐shock protein B8 (HspB8), which directly binds to both Nod1 and Nod2, prevents their aggregation and may enhance the assembly of active Nod1/2 oligomers . In epithelial cells, Nod1/2 signalling leads to the cellular and tissue restriction of pathogens through induction of pathogen‐directed autophagy, or xenophagy, and the production of barrier‐promoting proteins and AMPs, respectively (Figures and ) .…”
Section: Host Recognition Of Pg Metabolitesmentioning
confidence: 99%
“…16 These regulatory mechanisms include the newly discovered role of heat-shock protein B8 (HspB8), which directly binds to both Nod1 and Nod2, prevents their aggregation and may enhance the assembly of active Nod1/2 oligomers. 34 In epithelial cells, Nod1/2 signalling leads to the cellular and tissue restriction of pathogens through induction of pathogen-directed autophagy, or xenophagy, 35 and the production of barrier-promoting proteins and AMPs, respectively (Figures 2 and 3). 36,37 Moreover, activation of macrophages and other phagocytic myeloid cells elicits the direct killing of microbes and the clearance of host cells that present non-self signals from either internal pathogens or cancer-related mutations (Figures 2 and 3).…”
Section: Introductionmentioning
confidence: 99%